DEVELOPMENT OF EXPERIMENTAL POWER REACTOR (EPR) MODEL FOR SAFETY ANALYSES USING RELAP5 - Andi Sofrany Ekariansyah; Muhammad Subekti; Surip Widodo; Hendro Tjahjono; Susyadi Susyadi; Puradwi Ismu Wahyono; Anwar Budianto (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2019)
Pebble bed reactor design, classified as the high temperature gas-cooled reactor (HTGR), is currently being part of BATAN main program to promote nuclear energy by starting the Experimental Power Reactor (EPR) program since 2015. Starting from 2018, the detail design document has to be submitted into nuclear regulatory body for further assessment. Therefore results of design analysis have to be supplemented by performing a design evaluation, which can be achieved by developing the model of the EPR.  The development is performed using RELAP5/SCDAP/Mod.3.4 as the thermal-hydraulic analysis code validated for the light-water reactor having module for the pebble fuel element and non-condensable helium gas. Methodology of model development consists of defining the helium flow path inside the reactor pressure vessel, modelling of pebble bed core including its power distribution, and modelling of reflector components to be simulated under 100 % core power. The developed EPR model results in design parameters, which confirm the main thermal data of the EPR, including the pebble and reflector temperatures. The peak pebble temperature is calculated to be 1,375 °C, which requires further investigations in the model accuracy, since the reference values are around 1,015 °C, even it is below the pebble temperature limit. For safety analysis, the EPR model can be used under nominal core flow condition, which produces more conservative results by paying attention on the RELAP5 specific modules for the pebble bed-gas cooled system.Keywords: experimental power reactor, development, RELAP5, steady-state